PENGARUH PERILAKU PETANI DALAM PENERAPAN SAPTA USAHATANI TERHADAP PRODUKTIVITAS PADI DI KELOMPOK TANI VANDA SUBUR, KOTA SEMARANG - Darmawan, Arfiola; Gayatri, Siwi; Satmoko, Sriroso (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2021)
Vanda Subur Farmer Group is one of the largest rice-producing farmer groups in Semarang City. Pests and diseases are the obstacles faced by Vanda Subur Farmer Group. In handling these obstacles, the farmers referring to seven good farming practices so that Vanda Subur Farmer Group remains the largest rice-producing farmer group in Semarang City. The aims of the study were to: 1) analyze the farmer’s behavior in the application of seven good farming practices; 2) analyze the farmer’s behavior in the application of seven good farming practices toward rice productivity. This research was conducted from 2 February 2020 to 2 March 2020 in Vanda Subur Farmer Group, Semarang City. The method used in the study was a survey. The method of determining respondents was purposive sampling with 32 respondents from Vanda Subur Farmer Group. Data collection techniques were obtained from interviews using questionnaires and observations. Data were analyzed by descriptive analysis and multiple linear regression. The results showed that: 1) the knowledge, attitudes and skill farmers were in high criteria, 2) knowledge variable, attitude, and skill had a significant influence toward rice productivity, knowledge partially was not significant influencetoward rice productivity, meanwhile attitude and skill were not significant influence toward rice productivity. Increased productivity may occur when production increase.